Lateral aberrant thyroid having papillary carcinoma: a case report - Parab, Saurabh Subhash; Ghatage, Mansing N.; Kulkarni, Sharang S.; Patil, Aniket P.; Phatak, Pallavi S.; Hendre, Apurva P. (International Surgery Journal, 2021)
Aberrant thyroid is a mass of tissue having the structure of a pathological thyroid gland situated at some definite distance from the normal thyroid gland. In all the variants of carcinoma of thyroid the papillary variant is the most common. Predominantly seen in females ranging in the age group of 25-45 years. It is often well differentiated, slow growing and localised. Here we report a case of a 35-year-old lady with a swelling in the right anterior triangle of the neck with normal thyroid gland. Histopathological report was suggestive of papillary carcinoma of thyroid. The origin of lateral ectopic thyroid tissue is not fully understood and controversial. The lateral localisation is a rare entity and debated extensively in the literature. Though rare, the possibility of an ectopic thyroid carcinoma must always be considered by the surgeon in cases of a pathological mass in the neck. This case report demonstrates that a normal thyroid gland on clinical examination does not exclude the presence of thyroid carcinoma in an ectopic tissue.